The incidence of tooth loss and restorations in Al-Shamsiat Village - Nadira A Hatim; Ammar Kh Al-Nori; Sawsan H Al-Jubori (University of Mosul, College of Dentistry, 2004)
The aim of this research is to investigate the incidence of tooth loss, distribution of tooth loss in the oral cavity, the incidence of smoking habits and its rela-tion to tooth loss and to evaluate the motivation of patients to replace their missing teeth and their attitude toward the type of replacement, either fixed or removable in rural area (Al-Shamsiat village) in Nine-vah Governorate. A sample of 500 individual aged 15-70 years was selected randomly and examined using special chart prepared for this study. The results showed that 337 subjects were with partially missing of teeth. Three subjects (3.96%) with complete loss of teeth and the rest (160 subjects, 32%) were complete natural teeth. The study showed that there is no significant relationship between smoking and tooth loss. The motivation of patients was toward the type of prosthesis that are made mostly of removable acrylic type. A high percentage of population (64.86%) desire to replace their missing teeth in the village, which reflect the need of dental health, and dental treatment in the community.